Disease profile and Outcome of Newborn admitted to Neonatology unit of BPKIHS - Kanodia, Piush; Yadav, Sunil Kumar; Bhatta, Nisha Keshary; Singh, Rupa Rajbhandari (Journal of College of Medical Sciences-Nepal, 2015)
Background & Objectives: Neonatal period is a vulnerable time in which the newborn has to adapt to a totally new environment and is susceptible to many problems, which may even be life threatening. Every year, millions of neonates are born and a large proportion of them are admitted to the neonatal intensive care unit (NICU) for various indications. It is found that neonatal mortality rate is decreasing in Nepal but at a slower pace than infant and child mortality. In order to improve neonatal outcome, it is crucial to identify the areas where health care can be improved. Therefore, this study was conducted to identify the clinical profile, pattern of diseases and common causes of mortality and morbidity in neonates admitted to neonatology unit. Materials & Methods: A retrospective study was conducted at neonatology unit of BPKIHS, from January 2014 to December 2014. A total of 1009 neonates (both inborn and out-born) were admitted to neonatology division during the study period. Data was collected from the hospital record section. Ethical clearance was taken from the institutional ethical committee before the initiation of the study. Data was entered and descriptive analysis was done by using SPSS 20.0. Results: Total of 1009 neonates were admitted in neonatology unit. Among them, 349(34.5%) cases were admitted due neonatal sepsis, 236 (23.3%) due to prematurity and 233 (23.1%) with birth asphyxia. Among birth asphyxia, 102(43.7%) were in HIE III, 34.3% and 21.8% in HIE II and HIE I, respectively. The overall mortality was 47 (4.7%) during hospital stay. Conclusion: Sepsis, prematurity and birth asphyxia were major causes for admission in NICU. All these etiologies are preventable up to some extent and, if detected earlier, can be effectively treated in order to reduce morbidity and mortality JCMS Nepal. 2015;11(3):20-24.